MENJALANKAN RANGKAIAN STRATEGIS SAMUDERA BIRU (Suatu lde Penerapan di Perguruan Tinggi) - Chandra Utama (Bina Ekonomi, 2008)
To have its own blue ocean, university must be managed not in ordinary way. For example,,it should not only focus on its current customers but also on potential customers and change them to customers. Kim dan Mauborgne (2005) introduce four processes thaf university must do to have its own blue ocean. The processes include developing benefits for customers (why consumers buy), building strategic price, finding strategic cost, and adopting the strategy in organization. This paper introduces simple idea to build blue ocean strategy in university.